Evidence of nocturnal migration over sea and sex-specific migration distance of Dutch Black-Headed Gulls - Fijn, R.C.; Govers, L.L.; Lutterop, D.; Middelveld, R.P.; van Bemmelen, R.S.A. (Ardea, 2022)
Avian migration is recorded over long distances, but some species winter much closer to their breeding sites or do not migrate at all. Specifically, the family of gulls Laridae shows great within and among species variation in migration. However, the migration ecology of many gull species is still unknown, even for abundant and widespread species such as the Black-headed Gull Chroicocephalus ridibundus . Here, we aimed to map the migration of Black-headed Gulls using GPS-tracking data from eight birds from a declining colony at Griend in the Dutch Wadden Sea to study migration routes and timing as well as wintering habitat of these birds. Furthermore, we used this GPS-data and 199 colour-ring resightings of adult birds from the same colony to study their wintering locations and habitat. The GPS-tagged birds migrated away from the Dutch Wadden Sea between mid-September and late November. All migrated in western to south-western directions to wintering areas at 130 to 560 km from the breeding colony. The GPS-tagged individuals wintered in The Netherlands, France and the United Kingdom and migrated towards these wintering sites both diurnally and nocturnally. The data indicate that most movements over the North Sea were nocturnal, whereas most migratory movements over land were during the day. Colour-ring data showed that females wintered significantly further away than males. We found no indications for differences in timing of migration between males and females and also no sex-specific preference for nocturnal or diurnal migration. We argue that the hitherto undocumented prevalence of nocturnal sea crossings calls for a better assessment of the potential risks of offshore wind energy developments in the North Sea. As such, this and new GPS-tracking data of Black-headed Gulls can aid in the conservation of this common and widespread species by providing novel insights in migration behaviour and the connectivity between breeding and wintering grounds.